Location of inception point of alternating steps stepped spillways - Burhan S. Muhammed1; Kawa Z. Abdulrahman2 (Sulaimani Journal for Engineering Sciences, 2023)
This study explored the effects of flat-stepped spillways having alternating steps on the inception point location. Two wooden stepped spillways with a longitudinal slope of 26.6° were constructed in a rectangular flume and tested at various discharges, ranging from 0.003 to 0.05 m3/s. Each model had twenty-seven steps, and the channel's width, depth, and length were 0.605 meters, 1.35 meters, and 8 meters. The outcomes showed that the Alternating Model (MA), compared to the Regular Model (MR), has shortened the inception point distance (Li) from the downstream crest of the spillway by an average of 27% (e.g., the Li of the MR model was 59 cm, and the Li of the MA model was 43 cm). The MA model's skimming flow was discovered to begin at higher discharges, at yc/h 1.24 (as opposed to yc/h=0.98 for the MR model). Two equations were also developed to compute the inception point positions for flows over the MA and MR stepped spillways.